1998
DOI: 10.1542/peds.101.5.895
|View full text |Cite
|
Sign up to set email alerts
|

The Association Between Health Risk Behaviors and Sexual Orientation Among a School-based Sample of Adolescents

Abstract: GLB youth who self-identify during high school report disproportionate risk for a variety of health risk and problem behaviors, including suicide, victimization, sexual risk behaviors, and multiple substance use. In addition, these youth are more likely to report engaging in multiple risk behaviors and initiating risk behaviors at an earlier age than are their peers. These findings suggest that educational efforts, prevention programs, and health services must be designed to address the unique needs of GLB you… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

25
446
5
31

Year Published

1999
1999
2015
2015

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 683 publications
(509 citation statements)
references
References 16 publications
25
446
5
31
Order By: Relevance
“…Findings suggest that GLB youth have greater rates of depression, more suicide attempts (Fergusson et al, 1999), more risk taking behavior (Garofalo et al, 1998) (Cochran et al, 2002;Noell and Ochs, 2001;Whitbeck et al, 2004). Gender differences have also been noted by some researchers.…”
Section: Introductionmentioning
confidence: 58%
See 1 more Smart Citation
“…Findings suggest that GLB youth have greater rates of depression, more suicide attempts (Fergusson et al, 1999), more risk taking behavior (Garofalo et al, 1998) (Cochran et al, 2002;Noell and Ochs, 2001;Whitbeck et al, 2004). Gender differences have also been noted by some researchers.…”
Section: Introductionmentioning
confidence: 58%
“…One was that of a small sample size; a larger sample size could have generated more comparable group sizes and greater power to detect differences. However, a small sample size is a frequently reported limitation in studies conducted on this population (Cochran et al, 2002;Garofalo et al, 1998). Another limitation of this study is the fact that the original study was designed to examine treatment modalities for substance abusing homeless adolescents and not for comparison among the sample on sexual orientation.…”
Section: Limitationsmentioning
confidence: 99%
“…Literature also clearly documents disparities in smoking among lesbian, gay, and bisexual populations (i.e., sexual minorities) in the United States, suggesting 50%-70% higher prevalence than the general population (Austin et al, 2004;Garofalo, Wolf, Kessel, Palfrey, & DuRant, 1998;Gruskin, Greenwood, Matevia, Pollack, & Bye, 2007;Lee, Griffin, & Melvin, 2009;McCabe, Boyd, Hughes, & d'Arcy, 2003;Skinner, 1994;Stall, Greenwood, Acree, Paul, & Coates, 1999;Tang et al, 2004). Moreover, the American Lung Association (2010) published a special report of tobacco disparities among sexual minorities, harkening a call for more research.…”
Section: Introductionmentioning
confidence: 99%
“…Research in five sizable community samples has demonstrated increased risk (Faulkner and Cranston, 1998;Fergusson et al, 1999;Garofalo et al, 1998;Lock and Steiner, 1999;Remafedi et al, 1998). The increased risk for suicidal ideation and attempt behavior ranges from 2-fold (Faulkner and Cranston, 1998) to 7-fold (Remafedi et al, 1998).…”
Section: Risk Factorsmentioning
confidence: 99%